A Quality and Completeness Assessment of Testicular Cancer Health Information on TikTok - Hoi Pong Nicholas Wong; Lee Jing Yang; Vikneshwaren S/O Senthamil Selvan; Jamie Yong Qi Lim; Wei Zheng So; Vineet Gauhar; Ho Yee Tiong (Société Internationale d’Urologie Journal)
TikTok has become a hub for easily accessible medical information. However, the quality and completeness of this information for testicular cancer has not been examined. Our study aims to assess the quality and completeness of testicular cancer information on TikTok. A search was performed on TikTok using the search terms “Testicular Cancer” and “Testicle Cancer”. Inclusion criteria encompassed videos about testicular cancer in English. We excluded non-English videos, irrelevant videos, and videos without audio. We evaluated these videos using the DISCERN instrument and a completeness assessment. A total of 361 videos were considered for screening and 116 videos were included. Of these, 57 were created by healthcare professionals (HCPs). The median video length was 40 s (5–277 s), with >25 million cumulative views and a median of 446,400 views per video. The average DISCERN score was 29.0 ± 5.7, with HCPs providing higher-quality videos than non-HCPs (30.8 vs. 5.5, p < 0.05). HCPs also had more reliable videos (21.2 vs. 18.1, p < 0.05). Overall quality levels were mostly poor or very poor (97.4%), with none being good or excellent. Most HCP videos were poor (63.2%), whilst many non-HCP videos were very poor (61.0%). The most viewed video had 2,800,000 views but scored a 31 on the DISCERN tool and one on the completeness assessment. The highest DISCERN score had 11,700 views. HCP videos better defined the disease and were more complete (p < 0.05). Most videos discussed self-assessment but were lacking in definitions, risk factors, symptoms, evaluation, management, and outcomes. Most of TikTok’s testicular cancer information lacks quality and completeness, whilst higher-quality videos have limited reach.